2008
DOI: 10.1002/chir.20510
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in spirochalcogenurane stereochemistry—A mini review

Abstract: A summary of the present knowledge of the stereochemistry of the hypervalent spirochalcogenuranes, especially the role of the central atom (S, Se, Te) for the chemical and configurational stability and the chiroptical and X-ray crystallographic techniques available for the determination of absolute configuration, is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The thioselenurane in product complex 3f9 P 0 formed by following the reaction coordinate is in an unstable conformation 9 0 with the -SMe group trans to the amide. Pseudorotation to 9, the conformation with a trans arrangement of the most electronegative groups (amide and hydroxyl) of the three-center-four-electron bond, 84 should be rapid. 85 The rearranged product complex 3f9 P was 3.6 kcal/mol more stable than 3f9 P 0 and is predicted to be in equilibrium with the reactants (0.1 kcal/mol).…”
Section: ' Theoretical Methodsmentioning
confidence: 99%
“…The thioselenurane in product complex 3f9 P 0 formed by following the reaction coordinate is in an unstable conformation 9 0 with the -SMe group trans to the amide. Pseudorotation to 9, the conformation with a trans arrangement of the most electronegative groups (amide and hydroxyl) of the three-center-four-electron bond, 84 should be rapid. 85 The rearranged product complex 3f9 P was 3.6 kcal/mol more stable than 3f9 P 0 and is predicted to be in equilibrium with the reactants (0.1 kcal/mol).…”
Section: ' Theoretical Methodsmentioning
confidence: 99%
“…Spirodioxyselenuranes such as 2 and 4 are chiral. Stereochemical and chiroptical studies of certain related selenuranes have been reported, while several such compounds have been resolved and their absolute configurations determined . Other derivatives containing camphor moieties were obtained as pure diastereomers .…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of spirodioxysulfuranes has been studied extensively due to their interesting structural and stereochemical properties . In addition to the sulfur compounds, some selenium and tellurium analogues have also been studied . The first compound of this kind, spirodioxyselenurane 2 , was synthesized in 1914 by Lesser and Weiss .…”
Section: Introductionmentioning
confidence: 99%